Investasi dalam Bingkai Politik Luar Negeri Pemerintahan Jokowi Jilid Satu dan Dampaknya bagi Masyarakat Indonesia - Adi Saputro; Taufiequrrohman Taufiequrrohman (Universitas Medan Area, 2021)
In the framework of international politics, the economic dimension has a central role in relations between countries. The economic dimension, particularly investment, is a determinant factor and often becomes a global measure in achieving national development. This has also become President Jokowi's big ambition since he came to power in Indonesia. Various investments were brought in in the framework of national development and the implementation of the Nawa Cita ideals. The foreign policy which is very inclined to attract investors continues. Deregulation of domestic policies was also carried out in order to welcome investment. However, in fact, the investment that Jokowi brought and carried out did not change the lives of Indonesian people. Economic growth predicted to skyrocket has actually stagnated in the 5 years of his reign. The absorption of labor has also decreased. Not to mention other problems caused by the investment made.